Scalp shagreen patch: an unusual cutaneous manifestation of tuberous sclerosis complex: a case report - Abualiat, Abdullah; Elobeid, Wifag; Edris, Hala (International Journal of Research in Medical Sciences, 2017)
Tuberous sclerosis complex (TSC) is an inherited neurocutaneous disorder with multisystem involvement and highly variable expression of the disease. Common cutaneous manifestations include angiofibromas, periungual fibroma, ash-leaf-shaped macules and shagreen patch which is slightly elevated soft skin-coloured plaque usually found in lumbosacral region. We report a case of TSC in a 21- year- old Saudi man with a 13 years history of asymptomatic skin lesions and generalized tonic-clonic seizures. Dermatological examination revealed facial angiofibromas, ash leaf macules, pedunculated fibromas on trunk, and shagreen patch on the back. Scalp swelling was found and confirmed to be shagreen patch by the histopathology findings. In conclusion, scalp shagreen patch is an unusual presentation of TSC. It should be considered in clinical examination of suspected cases of TSC with relevant histopathology to confirm the lesion.